2023
DOI: 10.12998/wjcc.v11.i24.5700
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter-2 inhibitor-associated euglycemic diabetic ketoacidosis in COVID-19-infected patients: A systematic review of case reports

Anwar Khedr,
Hussam Al Hennawi,
Muhammed Khuzzaim Khan
et al.

Abstract: Alzheimer’s disease (AD) is a progressive and neurodegenerative illness which results in alterations in cognitive development. It is characterized by loss/dysfunction of cholinergic neurons, and formation of amyloid plaques, and formation of neurofibrillary tangles, among other changes, due to hyperphosphorylation of tau-protein. Exposure to pesticides in humans occurs frequently due to contact with contaminated food, water, or particles. Organochlorines, organophosphates, carbamates, pyrethroids and neonicoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The Umbrella review part of our study comprised 10 reviews: one systematic review of case reports 79 , six systematic reviews and meta-analyses 7,8,[80][81][82][83] , one meta-analysis 84 , and two network meta-analyses 4,57 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Umbrella review part of our study comprised 10 reviews: one systematic review of case reports 79 , six systematic reviews and meta-analyses 7,8,[80][81][82][83] , one meta-analysis 84 , and two network meta-analyses 4,57 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that there was a decreased risk of hospitalisation 54 and a reduced risk of requiring non-invasive or invasive mechanical ventilation 61 . While a review of case reports suggested a possible increase in the risk of euglycemic diabetic ketoacidosis 79 with SGLT2i, the level of evidence was deemed non-signi cant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations